Optimisation of cooperation of hybrid renewable energy sources with hydrogen energy storage toward the lowest net present cost - Łukasik, Jakub; Jewartowski, Marcin; Wajs, Jan (Instal, 2023)
The paper presents the results of a technical and economic analysis of the power supply for a model industrial facility based on intermittent renewable energy sources in the form of wind turbines and photovoltaic modules, supplemented with hydrogen energy storage. The adopted power supply strategy assumed the maximisation of self-consumption of self-produced electricity. Six variants were considered, including two with an energy storage system, three using only RES, and a reference variant in which the model facility is powered by the power grid. The modelling and optimisation of the proposed variants was carried out in the HOMER software, in terms of the lowest net present cost. The results obtained indicate that the most advantageous configuration is a grid-connected hybrid renewable energy system consisting of wind turbines and a photovoltaic power plant. A system with hydrogen energy storage is much more profitable than powering the facility from the grid. The profitability of hydrogen energy storage increases even more with the projected increase in electricity prices and the falling prices of hydrogen system components.
Keywords: hybrid renewable energy sources (HRES); economic analysis; environmental analysis; green hydrogen; fuel cell